2011
DOI: 10.1002/btpr.747
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study on the effect of dexamethasone in moderating cell death in Chinese Hamster Ovary cell cultures

Abstract: Dexamethasone (DEX) was previously shown (Jing et al., Biotechnol Bioeng. 2010;107:488-496) to play a dual role in increasing sialylation of recombinant glycoproteins produced by Chinese Hamster Ovary (CHO) cells. DEX addition increased sialic acid levels of a recombinant fusion protein through increased expression of α2,3-sialyltransferase and β1,4-galactosyltransferase, but also decreased the sialidase-mediated, extracellular degradation of sialic acid through slowing cell death at the end of the culture per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Our results are consistent with reports that DEX treatment ameliorates transfection-induced hMSC viability decrease as measured by WST-1 cell proliferation assay (Kelly et al, 2016). Furthermore, DEX has also been shown to rescue cytotoxicity and apoptosis induced in transfected HC92 rat cardiomyocytes (Kim et al, 2009), and reduced death of chinese hamster ovary (CHO) cells producing recombinant protein by modulating apoptosis-related gene expression (Jing et al, 2012). In addition to increasing transgenic protein synthesis, attenuation of apoptosis by DEX-priming could also promote the observed increase in relative transgenic enzyme HAMANN ET AL.…”
Section: Dex Ameliorates Hmsc Protein Synthesis Inhibition Induced supporting
confidence: 92%
“…Our results are consistent with reports that DEX treatment ameliorates transfection-induced hMSC viability decrease as measured by WST-1 cell proliferation assay (Kelly et al, 2016). Furthermore, DEX has also been shown to rescue cytotoxicity and apoptosis induced in transfected HC92 rat cardiomyocytes (Kim et al, 2009), and reduced death of chinese hamster ovary (CHO) cells producing recombinant protein by modulating apoptosis-related gene expression (Jing et al, 2012). In addition to increasing transgenic protein synthesis, attenuation of apoptosis by DEX-priming could also promote the observed increase in relative transgenic enzyme HAMANN ET AL.…”
Section: Dex Ameliorates Hmsc Protein Synthesis Inhibition Induced supporting
confidence: 92%
“…This suggests a model where Tsc22d3 is part of a negative feedback loop for the induction of a Th17 cell subtype that coproduce IL-17 and IL-10 and limits their pro-inflammatory capacity. Tsc22d3 is induced in other cells in response to the steroid Dexamethasone 41 , which represses Th17 differentiation and ROR-γt expression 42 . Thus, Tsc22d3 may mediate this effect of steroids.…”
Section: Resultsmentioning
confidence: 99%
“…The same group of researchers also reported 1.6-fold upregulation of Serpinh1 in low temperature and butyrate treated CHO cells that produced more IgG (Kantardjieff et al, 2010). Jing and colleagues observed that angiotensinogen (serpin peptidase inhibitor, clade A, member 8) was upregulated 2.15 fold in dexamethasone treated CHO cultures, and they associated the upregulation to the anti-apoptotic effects of dexamethasone (Jing et al, 2012). Most recently, Doolan et al concluded that Serpinf1 negatively correlated to growth rate in their transcriptomic studies on biomarker discovery for higher growth in CHO cells (Doolan et al, 2013).…”
Section: Discussionmentioning
confidence: 83%